Statin and mortality in COVID-19: a systematic review and meta-analysis of pooled adjusted effect estimates from propensity-matched cohorts. Issue 1161 (30th June 2021) - Zein, Ahmad Fariz Malvi Zamzam; Sulistiyana, Catur Setiya; Khasanah, Uswatun; Wibowo, Arief; Lim, Michael Anthonius; Pranata, Raymond
Abstract: Purpose: Statin potentially improved outcome in patients with COVID-19. Patients who receive statin generally have a higher proportion of comorbidities than those who did not, which may introduce bias. In this meta-analysis, we aimed to investigate the association between statin use and mortality in patients with COVID-19 by pooling the adjusted effect estimates from propensity-score matching (PSM) matched studies or randomised controlled trials to reduce bias. Methods: A systematic literature search using the PubMed, Scopus and Embase databases were performed up until 1 March 2021. Studies that were designed the study to assess statin and mortality using PSM with the addition of Inverse Probability Treatment Weighting or multivariable regression analysis on top of PSM-matched cohorts were included. The effect estimate was reported in term of relative risk (RR). Results: 14 446 patients were included in the eight PSM-matched studies. Statin was associated with decreased mortality in patients with COVID-19 (RR 0.72 (0.55, 0.95), p=0.018; I 2 : 84.3%, p<0.001). Subgroup analysis in patients receiving statin in-hospital showed that it was associated with lower mortality (RR 0.71 (0.54, 0.94), p=0.030; I 2 : 64.1%, p<0.025). The association of statin and mortality was not significantly affected by age (coefficient: −0.04, p=0.382), male gender (RR 0.96 (0.95, 1.02), p=0.456), diabetes (RR 1.02 (0.99, 1.04), p=0.271) and hypertension (RR 1.01 (0.97, 1.04), p=0.732) in this pooled analysis. Conclusion: In this meta-analysis of PSM-matched cohorts with adjusted analysis, statin was shown to decrease the risk of mortality in patients with COVID-19. PROSPERO registration number: CRD42021240137.